REINTERPRETATION OF NATIONAL FAMILY VALUES AGAINST THE BACKDROP OF CONTEMPORARY TRENDS (International Conference on Modern Science and Scientific Studies, 2025)
This article analyzes how national family values are reinterpreted amid contemporary trends—globalization, urbanization, the gender-equality discourse, and digital transformation—through a socio-philosophical lens. Drawing on conceptual and comparative analysis, it explicates the “integrative family model,” in which norms are adaptively selected, preserved, and renewed between tradition and modern demands, and examines how cultural identification underpins family stability. The paper traces shifts in family roles, changes in child-rearing practices, and the effects of policy-legal reforms that collectively restructure the value system. It proposes criteria for aligning modernization with the preservation of national distinctiveness. The findings provide a methodological basis for strengthening family resilience, enhancing social stability, and informing practical policy design.